TNNI3K is a novel mediator of myofilament function and phosphorylates cardiac troponin I - Wang,Hui (2013)
The phosphorylation of cardiac troponin I (cTnI) plays an important role in the contractile dysfunction associated with heart failure. Human cardiac troponin I-interacting kinase (TNNI3K) is a novel cardiac-specific functional kinase that can bind to cTnI in a yeast two-hybrid screen. The purpose of this study was to investigate whether TNNI3K can phosphorylate cTnI at specific sites and to examine whether the phosphorylation of cTnI caused by TNNI3K can regulate cardiac myofilament contractile function. Co-immunoprecipitation was performed to confirm that TNNI3K could interact with cTnI. Kinase assays further indicated that TNNI3K did not phosphorylate cTnI at Ser23/24 and Ser44, but directly phosphorylated Ser43 and Thr143 in vitro. The results obtained for adult rat cardiomyocytes also indicated that enhanced phosphorylation of cTnI at Ser43 and Thr143 correlated with rTNNI3K (rat TNNI3K) overexpression, and phosphorylation was reduced when rTNNI3K was knocked down. To determine the contractile function modulated by TNNI3K-mediated phosphorylation of cTnI, cardiomyocyte contraction was studied in adult rat ventricular myocytes. The contraction of cardiomyocytes increased with rTNNI3K overexpression and decreased with rTNNI3K knockdown. We conclude that TNNI3K may be a novel mediator of cTnI phosphorylation and contribute to the regulation of cardiac myofilament contraction function.